Up-conversion luminescence of GdVO4:Nd3+/Er3+ and GdVO4:Nd3+/Ho3+ T phosphors under 808 nm excitation - Jovanović, Dragana J.; Gavrilović, Tamara V.; Dolić, Slobodan D.; Marinović-Cincović, Milena; Smits, Krisjanis; Dramićanin, Miroslav D. (Elsevier B.V., 2018)
In recent years, there exists a tendency in research of up-conversion materials to shift excitation from 980 nm to shorter wavelengths. Here, in order to produce up-conversion luminescence emission of GdVO4-based materials under 808 nm excitation, polycrystalline powders of GdVO4:Er3+/Nd3+ and GdVO4:Ho3+/Nd3+ were successfully prepared by a high-temperature solid-state reaction technique. The prepared powders were highly crystalline with a single-phase zircon-type GdVO4 structure and consisted of micrometer-sized irregular spherical particles (2–6 μm in diameter). In all studied samples, visible up-conversion luminescence was successfully achieved under 808 nm illumination. Near-infrared pumping produced emission bands in the green, yellow-orange and green regions of the visible spectrum. The bands in the green and red regions of GdVO4: Er3+/Nd3+ as well as GdVO4:Ho3+/Nd3+ were, respectively, characteristic of Er3+ and Ho3+ ions. The dominant band originating from the 4G7/2 → 4I11/2 transition in Nd3+ ions was observed around 597 nm in all samples.
All authors acknowledge to the COST Action CM1403: The European upconversion network - from the design of photon-upconverting nanomaterials to biomedical applications (2014–2018). The authors from the University of Belgrade acknowledge the financial support of the Ministry of Education, Science and Technological Development of the Republic of Serbia (Project Nos. 45020 and 172056 ). K. S. acknowledges the Latvian National Research Program IMIS2 (Grant No. 302/2012 ). T. G. acknowledges the ERDF PostDoc project No. 1.1.1.2/VIAA/1/16/215 ( 1.1.1.2/16/I/001 ).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; 808-nm excitation; Gadolinium vanadate; GdVO4:Er3+/Nd3+; GdVO4:Ho3+/Nd3+; Up-conversion